Penyuluhan Ekonomi Syariah bagi Generasi Milenial - Wahyudi, Heru; Usman, Moneyzar; Palupi, Widia Anggi (Jurnal Abdimas Multidisiplin, 2023)
Purpose: The purpose of this activity is to increase the knowledge of the millennial generation about the urgency of the Islamic economy so that the millennial generation has enthusiasm to learn about the Islamic economy. This is appreciated by studying Islamic economics to increase the understanding of the millennial generation and can be implemented in everyday life. Research methodology: The method used in this service is classroom learning or training in the form of lectures, discussions, questions, and answers given to all participants involved in this activity. The participants in this activity were students of the Faculty of Economics and Business, University of Lampung, with as many as 80 people. Participants were selected because their age was very potent in increasing their understanding of the Islamic economy. Results: The material presented included an introduction to the basics of the Islamic economic economy, the urgency of the Islamic economy, and the Islamic economic community, successfully absorbed by 90% of participants with a value of A and the rest with a value of B. Limitations: The limitations of community service need to improve the use of technology, such as when conducting post-tests. Contribution: This activity causes the knowledge of the Islamic economy that has been obtained to be rounded and invites blessings and rejects reinforcements.